Choroidal morphology and the outer choroidoscleral boundary in dry age related maculopathy in Swept Source Optical Coherence Tomography - Trebinska, Magdalena; Michalewski, Janusz; Nawrocki, Jerzy; Michalewska, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Background and objective : To report on details of the choroid in dry age-related macular degeneration imaged with Swept Source Optical Coherence Tomography. Material and methods : Swept Source Optical Coherence Tomography was performed in 28 eyes with dry age-related macular degeneration (Group 1), who were age and refractive error-matched with 28 eyes of 28 healthy controls (Group 2). The visibility and contour of the outer choroidoscleral boundary and suprachoroidal layer was estimated. Results : Choroidoscleral boundary was visible in all eyes, irregular in 78% in Group 1 and in 18% in Group 2. Suprachoroidal layer was visible in 36% eyes in Group 1 and in 7% eyes in Group 2. Mean choroidal thickness did not differ between groups (p=.11). Conclusions : The outer choroidoscleral boundary is irregular in most cases of age-related macular degeneration. Suprachoroidal layer and suprachoroidal space are more often visible in dry age-related macular degeneration than in healthy controls.